Pengembangan Modul Keanekaragaman Hayati Berbasis Pangan Tradisional Nusa Tenggara Timur - Tpoenifu, Evi Yulinda; Mamangkey, Jendri; Silalahi, Marina (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aimed to develop a module for biology based on the local wisdom of East Nusa Tenggara (NTT) traditional cuisine for high school students, particularly for the 10th grade, focusing on the topic of biodiversity. This also focused on assessing the feasibility of the module and evaluating students' responses to its development.The development model used in this study was research and development (R&D), involving several stages of potentials and problems, data collection, product design, design validation, and design revision followed by collecting students’ responses to the module.The validation results from content experts, media experts, and language experts indicated that the local wisdom-based biology module was deemed valid. The average scores obtained from each expert's validation are as follows, content validation with a score of 0.81 in the "strongly valid" category as well as media validation with a score of 0.80 and language validation with a score of 0.79 in the "valid" category.The result related to students’ responseswas also highly positive with an average percentage of 88,8% in the "excellent" category. This study is expected to serve as a learning resource for students, helping them understand the biodiversity material that is correlated with local wisdom. It aims to provide students with values of local wisdom and contribute to the preservation of environmental traditions.